ORDERING METHODS OF C-CONTROL CHARTS WITH INTERVAL TYPE-2 INTUITIONISTIC FUZZY SETS - DEMİRALP, Sibel; HAÇAT, Gülnur (Journal of Universal Mathematics, 2020)
The control charts are important because it provides information about the process and the state of control of the product. With this feature, control charts are used in many areas. Intuitionistic fuzzy sets and interval valued intuitionistic fuzzy sets are useful to modelling of the real world problems. Ordering of the fuzzy numbers is investigated by a lot of scientists and it is generalised to intuitionistic fuzzy sets because of applicability. Ordering interval-valued type-2 intuitionistic fuzzy sets is significant in making decision, data analysis and artificial intelligence since interval analysis is required. In this study a new method to ordering interval-valued type-2 intuitionistic fuzzy sets is defined and numerical methods are compared to other methods.
Keywords: Interval type-2 intuitionistic fuzzy sets; Fuzzy control charts; c-Control charts; ordering methods; Matematik; Mathematical Sciences